Bomidin: An Optimized Antimicrobial Peptide With Broad Antiviral Activity Against Enveloped Viruses - Liu, Rongrong; Liu, Ziyu; Peng, Haoran; Lv, Yunhua; Feng, Yunan; Kang, Junjun; Lu, Naining; Ma, Ruixue; Hou, Shiyuan; Sun, Wenjie; Ying, Qikang; Wang, Fang; et al. (Frontiers in Immunology, 2022)
The rapid evolution of highly infectious pathogens is a major threat to global public health. In the front line of defense against bacteria, fungi, and viruses, antimicrobial peptides (AMPs) are naturally produced by all living organisms and offer new possibilities for next-generation antibiotic development. However, the low yields and difficulties in the extraction and purification of AMPs have hindered their industry and scientific research applications. To overcome these barriers, we enabled high expression of bomidin, a commercial recombinant AMP based upon bovine myeloid antimicrobial peptide-27. This novel AMP, which can be expressed in Escherichia coli by adding methionine to the bomidin sequence, can be produced in bulk and is more biologically active than chemically synthesized AMPs. We verified the function of bomidin against a variety of bacteria and enveloped viruses, including severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), herpes simplex virus (HSV), dengue virus (DENV), and chikungunya virus (CHIKV). Furthermore, based on the molecular modeling of bomidin and membrane lipids, we elucidated the possible mechanism by which bomidin disrupts bacterial and viral membranes. Thus, we obtained a novel AMP with an optimized, efficient heterologous expression system for potential therapeutic application against a wide range of life-threatening pathogens.